2017
DOI: 10.1017/s0959269517000084
|View full text |Cite
|
Sign up to set email alerts
|

Usage and processing of the French causal connectives ‘car’ and ‘parce que’

Abstract: The difference between ‘car’ and ‘parce que’ is often explained in the literature by the type of causal relation (objective or subjective) that each connective prototypically conveys. Recent corpus studies have demonstrated, however, that this distinction does not hold in speech, and is fluctuating in writing. In this article, we present new empirical data to assess the status of this pair of connectives. In Experiment 1, we test French-speakers’ intuitions about ‘car’ and ‘parce que’ in a completion task, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…In studies on discourse processing and representation, the difference between positive and negative relations is a classical finding, going back to Clark and Clark (1977). The special status of causal relations found by many researchers (Graesser et al 1994;Noordman and Vonk 1998;Sanders and Noordman 2000;Sanders and Spooren 2009a;Singer et al 1992;van den Broek 1990) corroborates the relevance of basic operation, and recent eye-tracking studies have shown that subjective relations are harder to process than objective ones, in English (Traxler et al 1997), Dutch (Canestrelli et al 2013) and French (Zufferey et al 2018). Evidence for the primitive implication order comes from processing experiments (Noordman and de Blijzer 2000), in which it is shown for objective or content-relations that a basic cause-consequence order is easier to process than a non-basic consequence-cause order.…”
Section: Empirical Evidence For Ccr-dimensionssupporting
confidence: 58%
“…In studies on discourse processing and representation, the difference between positive and negative relations is a classical finding, going back to Clark and Clark (1977). The special status of causal relations found by many researchers (Graesser et al 1994;Noordman and Vonk 1998;Sanders and Noordman 2000;Sanders and Spooren 2009a;Singer et al 1992;van den Broek 1990) corroborates the relevance of basic operation, and recent eye-tracking studies have shown that subjective relations are harder to process than objective ones, in English (Traxler et al 1997), Dutch (Canestrelli et al 2013) and French (Zufferey et al 2018). Evidence for the primitive implication order comes from processing experiments (Noordman and de Blijzer 2000), in which it is shown for objective or content-relations that a basic cause-consequence order is easier to process than a non-basic consequence-cause order.…”
Section: Empirical Evidence For Ccr-dimensionssupporting
confidence: 58%
“…For instance, Zufferey (2012) reports that these two connectives are interchangeable in many objective and subjective contexts when written, especially among the younger population of French native speakers. Moreover, some recent studies have questioned the subjective character of car (Zufferey et al 2018), and other researchers report that car can also be used to express objective relations (Nazarenko 2000).…”
Section: (4)mentioning
confidence: 99%
“…Given the relative difficulty of straightforwardly relating the use of car with the expression of subjective types of relation, an alternative hypothesis on the contemporary use of car has been proposed, according to which its use tends to be restricted to high register language, especially in (formal) writing such as newspaper articles (Zufferey 2012;Zufferey et al 2018). This observation is in line with the fact that car is much less attested in oral speech, is even considered extinct in contemporary spoken French (Fagard & Degand 2012), with its use in written texts fluctuating (Frei 1982(Frei /1929Bentolila 1986;Fagard & Degand 2008;Zufferey 2012).…”
Section: (4)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the situation varies dramatically in spoken texts since car is absent and parce que is used significantly more often in speech-act and epistemic relations. Zufferey et al, (2017) also provided empirical evidence that register is a distinguishing factor between connectives car and parce que. A final example is our previous study, in which we identified a significant relationship between the use of Spanish causal connectives and text type (informative versus persuasive/argumentative texts) in journalistic texts and between the use of Spanish causal connectives, text type (informative and persuasive/argumentative texts) and domain (Education and Psychology) in academic texts (Santana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%